Методика побудови онтолого-керованих інформаційних ресурсів як елементу комп'ютерних ділових ігор для навчання фахівців у галузі екологічної безпеки - Попова, М.А. (Екологічна безпека та природокористування, 2012)
The expediency of usage of computer business games in ecological education is considered. Method of forming of virtual educational and research environment on the basis of construction of ontology-operated information resources for computer business game is offered.